Prognostic and therapeutic impact of the KRAS G12C mutation in colorectal cancer - Qunaj, Lindor; May, Michael S.; Neugut, Alfred I.; Herzberg, Benjamin O. (Frontiers in Oncology, 2023)
KRAS G12C mutations are critical in the pathogenesis of multiple cancer types, including non-small cell lung (NSCLC), pancreatic ductal adenocarcinoma (PDAC), and colorectal (CRC) cancers. As such, they have increasingly become a target of novel therapies in the management of these malignancies. However, the therapeutic success of KRAS G12C inhibitors to date has been far more limited in CRC and PDAC than NSCLC. In this review, we briefly summarize the biochemistry of KRAS targeting and treatment resistance, highlight differences in the epidemiology of various G12C-mutated cancers, and provide an overview of the published data on KRAS G12C inhibitors for various indications. We conclude with a summary of ongoing clinical trials in G12C-mutant CRC and a discussion of future directions in the management of this disease.